The commodity system of "fourth range" salads in Italy: information technologies, logistics and the "fear of foreign bodies" - Lo Cascio, Martina; Perrotta, Domenico (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2021)
This article focuses on the commodity system of “fourth range” salads in Italy, in particular in the province of Bergamo (Lombardia region, Northern Italy) and in the Piana del Sele (Campania region, Southern Italy). With the aim of contributing to the debate on the "Made in Italy food consensus”, with its idea of ​​quality linked to tradition and environmental sustainability, we focus on a production with a very different definition of what “quality” means: the fourth range commodity system proudly represents itself as “industrial” and based upon innovations in technology; it tends to overshadow the relationship with traditions and typicality, it poses problems of environmental sustainability and considers the “land” itself as a problem and not as a value. Fourth range products are mostly distributed by big retail chains and, over the last thirty years, they have represented an innovation in production, processing and consumption. After a short description of the structure of this commodity system, we move to the analysis of the interviews, focusing on two issues: first, the importance of information technology and logistics and, second, the representation of this food as a “service” as well as a “product”, and in which the presence of “foreign bodies” in the plastic bags is considered something that must be absolutely avoided. The article is based on qualitative empirical research, in particular on 58 in-depth interviews, with farmers and farmworkers; workers, managers and technicians of processing plants; representatives of labour cooperatives, producer organizations, and trade unions, in both Lombardy and Campania.